Technical Note: Silo Type for Laboratory Scale Experiment on the Silage Quality - Paradhipta, Dimas Hand Vidya; Hidayah, Kharisma Taufiqa; Sari, Putri Candrika; Firdaus, Nu'man; Astuti, Andriyani; Joo, Young Ho (Buletin Peternakan, 2024)
The present study was aimed to investigate the effects of silo type for laboratory scale on chemical compositions, fermentation characteristics, and microbial counts of silage. Four typical silos use on a laboratory scale, consisting of transparent plastic bags (Silo A), black plastic bags (Silo B), transparent plastic bags covered with a bucket (Silo C), and transparent plastic bags covered with a sack (Silo D). All silo types were used to ensilage 5 kg Elephant grass (Pennisetum purpureum cv. Mott) for 21 d. Each Silo was conducted in triplicate. After ensiling, Silo C had higher crude protein with lower ammonia compared to other Silos (p<0.05). In addition, the Silo C resulted in lower pH, butyrate, and yeast with higher lactate and lactic acid bacteria (p<0.05) compared to other Silos. Silo C had the lowest bulginess, which indicated the optimum ensiling process. The present study concluded that ensiling forage with Silo C is more suitable and recommended for laboratory scale, which can reduce the errors, especially in the nutrient loss, production of ammonia, lactate, and butyrate, and also the counts of microbes in the silage.